Argon plasma coagulation versus cold steel tonsillectomy: a comparison of safety and efficacy - Zhen, Emily; Shaw, Chi-kee Leslie (Australian Journal of Otolaryngology; Vol 2 (October 2019): Australian Journal of Otolaryngology, 2019)
Background: Various tonsillectomy techniques have been introduced as alternatives to cold steel (CS) dissection. The aim of this study was to compare safety and efficacy of Argon plasma coagulation (APC) with CS tonsillectomy, by evaluating: (I) operative time; (II) intraoperative haemorrhage; (III) postoperative pain and (IV) postoperative haemorrhage. Methods: This study was a retrospective analysis of a 5-year prospectively collected database. Five hundred patients who underwent elective tonsillectomies performed by a single surgeon were included in this study (age range 1–57, male/female ratio =0.68, APC group n=232, CS group n=268). Results: APC group had shorter operative time than CS [12.33 min, standard deviation (SD) 0.284 vs. 20.68 min, SD 0.16, P